Inhibitory effect of gene combination in a mouse model of colon cancer with liver metastasis - DU, TONG (D.A. Spandidos, 2014)
The aim of the present study was to establish an animal liver metastasis model with human colon cancer and investigate the inhibitory effect of the wild type (WT) p53 gene combined with thymidine kinase/ganciclovir (TK/GCV) and cytosine deaminase/5-fluorocytosine (CD/5-FC) systems on liver metastasis of colon cancer. A nude mouse liver metastasis model with human colon cancer was established via a spleen cultivation method. A total of 32 nude mice were randomly divided into four groups, each group with eight mice. Group 1 mice received splenic injections of SW480 cells (control group), while group 2 mice were injected with SW480/p53 cells in the spleen. Group 3 mice were administered splenic injections of SW480/TK-CD cells, and GCV and 5-FC were injected into the abdominal cavity. Finally, group 4 mice received splenic injections of SW480/p53 cells mixed in equal proportion with SW480/TK-CD cells, as well as GCV and 5-FC injections in the abdominal cavity. These cells described were constructed in our laboratory and other laboratories. The number of liver metastatic tumors, the liver metastasis rate, conventional pathology, electron microscopy and other indicators in the nude mice of each group were compared and observed. The nude mouse liver metastasis model with human colon cancer was successfully established; the liver metastasis rate of the control group was 100%. The results demonstrated that the rate of liver metastasis in the nude mice in each treatment group decreased, as well as the average number of liver metastatic tumors. Furthermore, the effect of the treatment group with genetic combination (group 4) was the most effective, demonstrating that WTp53 had a synergistic effect with TK/GCV and CD/5-FC. Therefore, the present study successfully established a mouse model of liver metastasis with colon cancer by injecting human colon cancer cells in the spleen. Combined gene therapy was shown to have a synergistic effect, which effectively inhibited the formation of liver metastasis from colon cancer.